2003
DOI: 10.1142/s0192415x03001090
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Herpes Simplex Virus Activity of Bidens pilosa and Houttuynia cordata

Abstract: The present study evaluated the antiviral activity of Bidens pilosa L. var. minor (Blume) Sherff and Houttuynia cordata Thunb., using cytotoxicity test with XTT-based colorimetric assay. BCC-1/KMC cells were infected with herpes simplex virus (HSV) and then were cultured with hot water extract of B. pilosa (HWBP) or H. cordata (HWHC). Results showed that HWBP significantly inhibited the replication of HSV at a concentration of 100 microg/ml (11.9% for HSV-1, p < 0.01; 19.2% for HSV-2, p < 0.005), whereas HWHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 16 publications
3
65
0
4
Order By: Relevance
“…It provides a wide range of pharmacological activities including antiviral [7,8], antileukemic [9], antioxidative and antimutagenic effects [10,11]. Medicinal properties claimed for the drug have been attributed to its volatile oil [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It provides a wide range of pharmacological activities including antiviral [7,8], antileukemic [9], antioxidative and antimutagenic effects [10,11]. Medicinal properties claimed for the drug have been attributed to its volatile oil [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The lowest antiviral concentration needed for each was 4.5, 2.25 and 14 mg/mL, respectively . Chiang et al (2003) evaluated the antiviral activity of H. cordata using a cytotoxicity test with an XTT-based colorimetric assay. BCC-1/ KMC cells were infected with herpes simplex virus (HSV) and then were cultured with a hot water extract of H. cordata (HWHC).…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Since ancient times, H. cordata has been used in China as an edible vegetable and effective traditional Chinese medicine (TCM). It has a wide range of benefits including an antileukemic effect (Kwon et al, 2003), antimutagenic effect , anti-inflammatory action (Chiang et al, 2003), and antianaphylaxis effect , as well as the ability to promote immunologic function. Hayashi et al (1995) reported on its antileukemic activity and virucidal effects on the human immunodeficiency virus (HIV).…”
Section: Introductionmentioning
confidence: 99%
“…Hottuynia cordata Thunb is a perennial herb that is native to Southeast Asia (18) and it has a thin stalk and heart-like leaf. It is called E-Sung-Cho in China and it is known to be an effective drug for treating allergic inflammation (19).…”
Section: Introductionmentioning
confidence: 99%